EXPLORING ENTREPRENEURIAL MINDSET DEVELOPMENT THROUGH AGRIBUSINESS TOURISM FIELD TRIPS IN LAWANG - Dieva Zahrohtu Anfi; Rayyan Sugangga; Putria Dewi Masruroh; Iradah Rahman; Dewi Suwahibatul; Anistya Azzahra (Akademika : Jurnal Manajemen, Akuntansi, dan Bisnis., 2026)
Entrepreneurship education in higher education institutions often faces challenges in connecting classroom-based theories with real-world business practices. This study explores how experiential learning through agribusiness tourism field trips contributes to the development of entrepreneurial mindset among university students. The research was conducted using a qualitative descriptive approach with a case study design involving students from STIE Indonesia Malang who participated in educational visits to two agribusiness tourism destinations in Lawang, East Java: Graha Wiyata Outbound Psychology and Flora Education and Honey Harvest Tourism. Data were collected through in-depth interviews, participatory observation, focus group discussions, and documentation analysis. The findings indicate that direct exposure to agrientrepreneurial ecosystems enhances students’ entrepreneurial awareness, creativity, resilience, and opportunity recognition. At Graha Wiyata, students learned ornamental plant cultivation, plant propagation techniques, and agribusiness management practices. Meanwhile, at Wisata Petik Madu Lawang, students explored honey bee cultivation, honey harvesting, product diversification, and value-added product innovation, such as beeswax processing. The experiential learning process encouraged students to shift their mindset from job-seeking orientation toward opportunity creation and local resource-based entrepreneurship. The study concludes that agribusiness tourism-based experiential learning can serve as an effective pedagogical strategy for strengthening entrepreneurship education in higher education by integrating practical engagement, reflective learning, and real-world business exposure.